Perbandingan Area Inefsiensi Antara Nilai Pajak dan Zakat - Muthia Faridatunnisa; Mochamad Edman Syarief; Endang Hatma Juniwati (Journal of Applied Islamic Economics and Finance, 2021)
Tax policies set by the government can cause inefficiencies. Zakat policy is expected to minimize these inefficiencies. This research will try to compare how much inefficiency area caused by the value of tax and zakat. The data used is secondary data in the form of production from five business sectors found in Gross Domestic Product based on 2010 constant prices for the 2014-2018 period from the Central Bureau of Statistics. In this study quantitative calculations were carried out to determine the tax value, zakat value, and the area of triangle inefficiency, then after obtaining the results it would be compared to the magnitude of the triangle of inefficiency based on the value of tax and zakat. Different tests were carried out using SPSS to see whether the difference was significant or not. From the results of independent sample t-test, it is known that there are significant differences between the areas of inefficiency of the tax value and the value of zakat. This states that zakat produces inefficiency areas smaller than taxes.